Clinical Analysis of Multiple Primary Malignant Tumors: A Single-Center Experience - Bedir, Şahin; Samancı, Nilay Şengül; Çelik, Emir; Oruç, Kerem; Değerli, Ezgi; Derin, Sümeyra; Alkan Şen, Gülin; Şentürk Öztaş, Nihan; Özgüroğlu, Mustafa; Turna, Zeynep Hande; et al. (Cerrahpaşa Medical Journal, 2025)
Objective: Multiple primary malignant tumors (MPMTs) are at least 2 separate malignancies that develop independently. The incidence of patients diagnosed with MPMT is reported to be between 0.52% and 11.7% in various studies in different countries. The study aims to investigate the incidence, clinical features, and survival of patients with MPMT. Methods: About 121 patients diagnosed with MPMT in the institution were retrospectively analyzed between January 2015 and December 2020. Multiple primary malignant tumors were defined as synchronous tumors if they occurred within 6 months or less, and as metachronous tumors if they occurred more than 6 months. All statistical analyses were performed using SPSS version 25.0. Results: This study found the incidence of patients with MPMT was 2.6%. Two primary malignancies were detected in 104 (85.9%) patients, 3 primary malignancies in 13 (10.7%), and 4 primary malignancies in 4 (3.3%). In this study, the most common tumor associations were found in patients with MPMT were lungcolorectal 12 (7.1%), lung-prostate 9 (5.3%), and prostate-bladder 9 (5.3%) tumors. Among the patients with MPMT, 38 (31.4%) synchronous MPMT, 72 (59.5%) metachronous MPMT, and 11 (9%) both synchronous and metachronous MPMT were found. Conclusion: As a result, it was found that lung, colorectal, and prostate cancers were most common in MPMT patients. This study showed that it is very important to distinguish between second primary, recurrence, or metastasis and that treatment methods can be applied to cure patients with the correct diagnosis.